Characterizing acute respiratory infections in primary care for better management of viral infections - Hortense Petat; Matthieu Schuers; François Le Bas; Xavier Humbert; Andry Rabiaza; Sandrine Corbet; Astrid Vabret; Meriadeg AR Gouilh; Christophe Marguet (npj Primary Care Respiratory Medicine)
Abstract Acute respiratory infections (ARI) are the most common infections in the general population and represent an important socio-economic burden. Characterizing ARIs in primary care in patients of all ages in terms of clinical presentation, and virological results. We conducted a prospective multicenter study in primary care: 36 French general practitioners (GPs) included patients from all ages presenting with symptoms of ARI, and performed a nasopharyngeal swab, which was analyzed by Multiplex RT-PCR. 685 patients of all ages were included in the cohort. We found associations between clinical diagnosis and respiratory viruses: influenza was associated with the diagnosis of flu-like syndrome (p < 0.001), HRV with rhinitis (p < 0.05), and RSV with bronchiolitis (p < 0.001) and bronchitis (p < 0.05). Respiratory distress was associated with RSV (p = 0.002), and a cough at the inclusion was significantly not associated with the influenza virus (p = 0.009). Antibiotic prescriptions were not associated with any specific virus. By day 7, persistent cough was significantly associated with active and passive smoking (respectively p = 0.01 and p < 0.001), influenza and RSV-positive samples (p < 0.05) and an age of less than 2 years (p < 0.01). With this prospective cohort performed in primary care including patients of all ages, we characterized viral respiratory infections, to better understand correlations between clinical data and virological results.